The stabilizing role of forward guidance: A macro experiment - Steffen Ahrens; Joep Lustenhouwer; Michele Tettamanzi (Bamberg University, Bamberg Economic Research Group (BERG), 2018)
Expectations are among the main driving forces for economic dynamics. Therefore, managing expectations has become a primary objective for monetary policy seeking to stabilize the business cycle. In this paper, we study whether central banks can manage market expectations by means of forward guidance in a New Keynesian learning-to-forecast experiment. Forward guidance takes the form of one-period ahead inflation projections that are published by the central bank in each period. Subjects in the experiment observe these projections along with the historic development of the economy and subsequently submit their own one-period ahead inflation forecasts. In this context, we find that the central bank can significantly manage market expectations through forward guidance and that this management strongly supports monetary policy in stabilizing the economy. Moreover, forward guidance drastically reduces the probability of a deflationary spiral after strong negative shocks to the economy.
Keywords: C92; E32; E37; E58; 330; learning-to-forecast experiment; forward guidance; heterogeneous expectations